Sistem Penjadwalan Bel Sekolah Otomatis Berbasis RTC Menggunakan Mikrokontroler - Randi Rian Putra; Hamdani Hamdani; Soly Aryza; Nelly Astri Manik (STMIK Budi Darma, 2020)
Today's school bell technology has been transformed into an electricity-based school bell. An electric school bell is a technology that replaces school bells by hitting them to become a button based school bell to ring it. The purpose of this study is to build an automatic school bell scheduling system that is integrated with the ATMega328P microcontroller as a data processor, RTC (Real Time Clock) as a timer, Bluetooth as a liaison to smartphones to change subject schedules, and PAM8403 as a sound amplifier applicator that is connected to DFPlayer and Speaker. The system circuit is built using the microcontroller module ATMega328P, RTC DS3231 (Real Time Clock), Bluetooth HC05, DFPlayer, PAM8403. This research resulted in an automatic school bell scheduling system based on RTC using a microcontroller ATMega328P